Degradation of páramo vegetation due to cattle ranching in Parque Nacional Llanganates, Ecuador - Romo-Rojas, Mario Giovanni; Romo, Estefanía Calero (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
The research aimed to determine the degradation of the paramo vegetation due to the effect of livestock in Parque Nacional Llanganates. Two paramo zones with similar characteristics were established in Anteojos and Pisayambo Lake Complexes. By using the QGIS program and the shapefile at a scale of 1: 50000, sites with the presence and absence of livestock were delimited. Through direct observation, the number of cattle running through Pisayambo was counted, the herds were registered and georeferenced in a field card. The vegetative study was carried out by applying the minimum area technique, in each study area three sample units were taken. In the research instrument, the name of the species, frequency, presence scale, and status was recorded according to the criteria indicated in the literature consulted. The results show that in the surroundings of the Pisayambo Lake Complex there are 109 specimens of cattle and 12 horses. The highest dominance of plant species is found in the Anteojos Lacustrine Complex, this is reflected in the calculated value of the Simpson Diversity Index (0.901) compared to that obtained in Pisayambo (0.860). Species resistant to the presence of cattle are Calamagrostis intermedia, Lachemilla orbiculata and Plantago rigida. In conclusion, livestock produces a negative impact on the paramo vegetation and at the same time constitutes a serious problem for the management of Parque Nacional Llanganates.